Trajectory planning for all sub phases of gait cycle for human-like walking. (2nd February 2010) - Rai, J.K.; Tewari, R.P.; Chandra, Dinesh
This paper presents a cubic spline trajectory for all phases of gait cycle to achieve smooth human-like walking. We first characterise the human walking cycle into various sub-phases. A biped robot having seven links and six revolute joints has active hip, knee and ankle joints of both legs for human legs like appearance and walking performance. A mathematical cubic spline is developed for each phase of gait cycle. It uses the experimental flexion angle and velocity data of three joint movements i.e., hip, knee and ankle. The desired trajectory is developed as in case of normal human walking. The proposed trajectory has a standard deviation of less than 1°.